Empowerment of Orphanage Caregivers with the IHC Model to Improve Adolescent Psychological Needs - Siti Nur Kholifah (Frontiers in Community Service and Empowerment, 2022)
The caregiver is responsible for the psychological needs of adolescents. The purpose of this community service activity is to empower caregivers to fulfill the psychological integrity of adolescents by applying the Interpersonal Human Caring (IHC) model. This method of implementing community service activities is through identifying fulfillment of needs before and after empowerment, carrying out health education activities, identifying the role of caregivers before empowerment, the empowerment process, identifying roles after the empowerment process and identifying the psychological needs of adolescents after the empowerment process. This activity was carried out at the Khadijah 1 Orphanage, Khadijah 2 Orphanage, Aisyiah Orphanage, Mahbubiyah Orphanage, and Al Ikhlas Al Khoiriyah Orphanage. The number of teenagers is 60 people and the number of caregivers is 25 people. The results that have been achieved are an increase in the fulfillment of psychological needs in adolescents and an increase in the role of caregivers in meeting the psychological needs of adolescents. One of the recommended suggestions is the need for provision of caregivers by the Surabaya City Social Service so that they can care for adolescents by applying the Interpersonal Human Caring model so that the psychological needs of adolescents in orphanages throughout the city of Surabaya can be met.